Image Transmission Using SC-FDMA System Over mmWave Measured Channel at 29.5 GHz - Khelil, Abdellatif; Talbi, Larbi; Slimani, Djamel; LeBel, Jules (International Journal of Sensors Wireless Communications and Control, 2020)
Aims: This paper presents an investigation of image transmission using SC-FDMA system over wireless fading channels. Background: A comparison is performed between the performance of the wireless transmitted image over 3GPP LTE channel (vehicular and pederstain) and mmWaves measured channel at 29.5 GHz. Objectives: One of the important benefits of this work is the real measurement obtained at 29.5 GHz under NLOS scenario using an original sounder based on the ensuring of phase coherence between the transmitter and the receiver. Methods: Cameraman image has been transmitted over the SC-FDMA with different subcarriers mapping schemes. PSNR and MSE are the metrics used to evaluate the performance of the image transmitted under Matlab simulation where their values of the received image are calculated for different SNR values. Results and Conclusion: The simulation results show that the image transmission over mmWaves channel works and the best values of PSNR are attained beyond 12 dB and 14 dB for LSC-FDMA and ISC-FDMA respectively.
Keywords: 5G